Management of External Parasites with Forced-Use Dust Bags - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS)
Revised! ENY-281, a 7-page illustrated fact sheet by P. E. Kaufman, P. G. Koehler, and J. F. Butler, describes this safe, economical, and effective technique for managing external parasites on cattle in Florida — background, directions for hanging commercial dust bags, safety, cost of treatment, and effectiveness. Includes references. Published by the UF Department of Entomology and Nematology, April 2009.